Energy Marketing and Fiscal Regulation of a Competitive Energy Efficiency System - Kuzmynchuk, Nataliia; Kutsenko, Tetiana; Aloshyn, Serhii; Terovanesova, Oleksandra (Dr. Viktor Koval, 2024)
Introduction. Developing and implementing the principles of the energy-saving approach concept actualizes the need to define energy marketing tasks and fiscal regulation tools for energy conservation to increase the efficiency of using resources in the energy sector. Aim and tasks. The aim of this study is to form and substantiate the expediency of implementing directions for energy marketing development and fiscal regulation of implementing energy-saving measures to achieve the goals of national economic recovery and large-scale energy modernization. The results. The main tasks of energy marketing in monitoring the current world environment based on information and communication technologies have been defined and substantiated, and that should become a source of competitive advantage in the electric energy market and obtain significant income for market participants. It has been proven that using oligopoly models to determine the equilibrium condition of the electric energy market will make it possible to form a corrective managerial influence on the development of a competitive energy industry. With a 3-fold increase in the demand parameter, it has been established that the electricity market reaches equilibrium under the equilibrium model of supply functions with larger electricity production volumes and lower prices than in other models. It has been proposed to introduce tools for fiscal regulation by introducing energy-saving technologies into a single system of solutions to increase energy efficiency and energy saving. Conclusions. Analysing and generalizing the features of energy market participants’ interaction using a wide range of oligopoly models made it possible to develop recommendations for implementing strategic security-related tasks. If these tasks are not realized, the risks of losing energy independence will increase, and the economic potential necessary for the restoration and further development of the national economy will continue to be lost based on the principles of sustainable development and a systematic approach to setting and achieving the goal of the national energy-saving policy. The feasibility of introducing tools for budget regulation is also justified, which will create a robust creative basis for implementing an effective strategy for managing the demand for energy resources.